Gratitude predicts prosocial tendency through psychological resilience—cross-sectional study in Arab cultures - Alamri, Ayman Abdullah Hazza; Al-Abyadh, Mohammed Hasan Ali (Frontiers in Psychology, 2024)
This study aimed to investigate the relationship between gratitude and prosocial tendency and the potential mediating role of psychological resilience in this association. Six hundred and seventy-six Saudi Arabia and Egyptian students completed the Gratitude Scale, Prosocial tendency Scale and Psychological Resilience Scale. The results showed no significant differences in gratitude, prosocial tendency and psychological resilience according to culture or gender in both countries. Moreover, gratitude positively correlated with prosocial tendency and psychological resilience. Furthermore, the results revealed that psychological resilience significantly mediated the association between gratitude and prosocial tendency. We conclude that gratitude predicts prosocial tendency and psychological resilience plays a mediating role in this association among Arab societies.